2016
DOI: 10.1111/all.13059
|View full text |Cite
|
Sign up to set email alerts
|

IgE‐associated allergic disorders: recent advances in etiology, diagnosis, and treatment

Abstract: IgE-associated allergic diseases belong to the most common inflammatory conditions. Their clinical manifestation ranges from mild symptoms to life-threatening episodes. Often patients experience a reduction in physical and psychologic wellbeing and suffer from a decreased quality of life due to disease activity. The continuously rising number of people that are affected by an allergic condition indicates an urgent need for better diagnostics and more efficient treatment options. Recent progress in the understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 90 publications
0
33
0
1
Order By: Relevance
“…IgE is secreted by B cells that are stimulated by inhaled allergens; allergen-IgE cross-linking then triggers allergic inflammatory responses (1,33). Thus, a high IgE level is considered a risk factor for allergen-related symptoms, and it has been experimentally observed in several studies of allergic diseases (6,15,34,35). Recently, Cahenzli et al found that a gut microbiota with a low level of diversity would lead to increased IgE levels, which cause systemic anaphylaxis; however, a highly diverse gut microbiota does not lead to hyper-IgE (36).…”
Section: Discussionmentioning
confidence: 99%
“…IgE is secreted by B cells that are stimulated by inhaled allergens; allergen-IgE cross-linking then triggers allergic inflammatory responses (1,33). Thus, a high IgE level is considered a risk factor for allergen-related symptoms, and it has been experimentally observed in several studies of allergic diseases (6,15,34,35). Recently, Cahenzli et al found that a gut microbiota with a low level of diversity would lead to increased IgE levels, which cause systemic anaphylaxis; however, a highly diverse gut microbiota does not lead to hyper-IgE (36).…”
Section: Discussionmentioning
confidence: 99%
“…They involve a sensitization process including drug-induced activation of Th2 cells, producing specific IgE (sIgE). 137 These sIgEs bind to the FcεRI receptor on mast cells and basophils. In subsequent drug contacts, the simultaneous recognition by at least two sIgE initiates the degranulation and release of mediators.…”
Section: Ige-mediated Reactionsmentioning
confidence: 99%
“…Allergic diseases are complex and represent multiple phenotypes such as clinically silent IgE sensitization, isolated phenotypes such as only rhinitis, asthma, dermatitis, food allergy and multimorbidities associating several conditions in the same subject.…”
Section: Introductionmentioning
confidence: 99%